Color semantics in upholstery fabric designs and their spatial relationships (Journal of the College of Basic Education, 2022)
The research dealt with the color connotations used by the designer by describing color as one of the most important elements that contribute to the creation of the visual form, directing the recipient's visual perceptions, and considering it a visual stimulus in the design. Where the research aims to reveal the connotations of color and its spatial relationships in the design of furnishings, the limits of the research were limited to the study of color connotations and their spatial relationships in the designs of home furnishings.